Advances in Agricultural Economic History - Kauffman, Kyle D. (Amsterdam : Elsevier Science Ltd, 2003)
Volume two of Advances in Agricultural Economic History, like volume one, contains important new work by both established and young academics. Additionally, this recent volume reflects, both geographically and methodologically, the broad scope of cutting edge work being done in this area. It is this type of scholarship that we seek to publish in future issues. We invite scholars who work in all areas of agricultural economic history to submit their work for publication in future volumes of Advances in Agricultural Economic History.
Some issues also have distinctive titles.
Imprint varies.
Table of contents also available on the Internet.
Latest issue consulted: Vol. 2 (2003).
rpm 17/09/13
Loans
Keywords: Agriculture -- Economic aspects -- Periodicals; Industrialization -- Periodicals